Identifying and characterizing a member of the RhopH1/Clag family in Plasmodium vivax (2011)
Plasmodium vivax malaria caused is a public health problem that produces very high morbidity worldwide. During invasion of red blood cells the parasite requires the intervention of high molecular weight complex rhoptry proteins that are also essential for cytoadherence. PfClag9, a member of the RhopH multigene family, has been identified as being critical during Plasmodium falciparum infection. This study describes identifying and characterizing the pfclag9 ortholog in P. vivax (hereinafter named pvclag7). The pvclag7 gene is transcribed at the end of the intraerythrocytic cycle and is recognized by sera from humans who have been infected by P. vivax. PvClag7 subcellular localization has been also determined and, similar to what occurs with PfClag9, it co-localize with other proteins from the Rhoptry high molecular weight complex. © 2011 Elsevier B.V.